PERBEDAAN KEPUASAN KONSUMEN TERHADAP MENU DI CAFE DE ROSSA HARMONI SUITES HOTEL BATAM - Marisya "; Firdaus Yusrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aim to determine customer satisfaction on the menu that are not yet using a standard recipe, determine customer satisfaction on the menu that has been using the standard recipe and know the difference between the consumer satisfaction not yet using standard menu recipes and which has been using the standard recipe. This research is a field experiment. The population of this research is guest who ever eat and drink at Cafe de Rossa, a sample of this research were 200 respondents taken in stages, the first stage is done to the 100 consumers who consume the menu without using the standard recipe and the second stage at 100 those consumers who consume the menu using the standard recipe. Based on the research that has been done, that the difference in satisfaction of consumers who consume without using the standard menu recipes and menus that have been using the standard recipe.Keywords : Satisfaction, Consumer, Standard Recipes.